PENGARUH RENDAM AIR HANGAT PADA KAKI TERHADAP INSOMNIA PADA LANSIA DI DESA TENGAH KECAMATAN PANTAI LABU KABUPATEN DELI SERDANG TAHUN 2018 - Mestika Rija Helti; Dedi (Program Studi S1 & DIII-Kebidanan Universitas Imelda Medan, 2020)
Insomnia is a symptom experienced by clients when they experience chronic sleep difficulties, often waking up from sleep, and or short sleep or non-restorative sleep. Handling of insomnia in the elderly can be done with pharmacological and non pharmacological. One type of treatment of non-pharmacological insomnia in the elderly is soaking the feet with warm water. Soaking warm water on the feet is a sleep stimulation technique that is done by soaking the feet in warm water with a temperature of 37 ° C-39ºC. This study aims to determine the effect of warm water soak on the feet against insomnia in the elderly in Desa Tengah District Labu Beach, Deli Serdang Regency. This study uses a quasi-experimental type using one group pretest and posttest desaign methods. The population in this study were all elderly people in the Middle Village of hamlet I and hamlet II with ages above 60-74 years. The population obtained was 53 elderly. The sampling technique is done by using non-probability sampling method with purposive sampling technique obtained as many as 20 people. Analysis of the data used in this study is paired t-test. Hypothesis test results indicated by using paired t-test is a sig value of 0.000 (<0.05). This shows that there is an effect of warm water soak on the feet against insomnia in the elderly in Central Village Pantai Labu Subdistrict Deli Serdang Regency in 2018. The conclusion in this study is that there is an effect of warm water soak on the feet against insomnia in the elderly in the Central Village Pantai Labu District Deli Serdang 2018. Soaking feet with warm water can be used as an alternative measure to reduce insomnia and as a reference in efforts to improve the health of the elderly.